MRI-Based Treatment of Rectal Cancer: Is Prognostication of the Recurrence Risk Solid Enough to Render Radiation Redundant? - Sautter-Bihl, Marie-Luise; Hohenberger, Werner; Fietkau, Rainer; Roedel, Claus; Schmidberger, Heinz; Sauer, Rolf (Annals of Surgical Oncology, 2014)
Most current guidelines recommend neoadjuvant short course radiotherapy (sRT) or radio-chemotherapy (nRCT) for rectal cancer stage II and III. After the introduction of total mesorectal excision (TME) and magnetic resonance imaging (MRI), this proceeding has been questioned and omission of neoadjuvant treatment according to preoperative MRI-criteria has been propagated. Aim of the present paper is to review the state of evidence regarding MRI-based treatment decision depending on the predicted width of the circumferential resection margin (CRM).A comprehensive survey of the literature was performed using the search terms "rectal cancer", "radiotherapy", "radio-chemotherapy", "MRI-based therapy", "circumferential resection margin". Data from lately published observational studies were compared to results from randomized trials and outcome analyses of the Norwegian national cancer registry.Only one observational study using MRI-based treatment according to the anticipated CRM provided 5 year local recurrence data, however only for 65 patients. The second study did not yet evaluate recurrence rates. Two randomized trials comparing sRT to primary TME showed significantly worse outcome for non-irradiated patients. Data from the Norwegian rectal cancer registry demonstrate that TME alone is associated with higher LRR than achievable with preoperative RT.Current evidence does not support the omission of neoadjuvant treatment for stage II-III rectal cancer on the basis of an MRI-predicted negative CRM. Randomized studies are warranted to clarify whether and for which subgroups TME alone is safe in terms of local recurrences.
EVALuna2:15138